SYSTEMATIC JUVENILE ARTHRITIS: A MODERN VIEW ON PATHOGENESIS, DIAGNOSIS AND TREATMENT - Людмила Николаевна Игишева; Светлана Сергеевна Притчина (The Publishing House Medicine and Enlightenment, 2016)
Data about modern pathogenesis, clinical signs, diagnostics and treatment of systematic juvenile arthritis. You can find information about the differentiation diagnosis of disease with a Human Autoinflammatory Disease (HAIDS).